Voluntary Disclosure Credibility and Securities Prices: Evidence from Management Earnings Forecasts, 1969-73 - Pownall, Grace; Waymire, Gregory (Journal of Accounting Research, 1989)
Voluntary Disclosure, Credibility, Stock market reaction, Information content